Efficacy and safety of trastuzumab emtansine in older patients with HER2-positive advanced breast cancer: a real-world study - BAŞOĞLU TÜYLÜ, TUĞBA (SAGE PUBLICATIONS LTD, 2022)
Introduction: Ado-trastuzumab emtansine (T-DM1) is an antibody-drug conjugate and its survival advantage has been shown in advanced human epidermal growth factor receptor 2 (HER2)-positive breast cancer. However, clinical trials underrepresent patients > 65 years of age, leading to a lack of information in this population. We analyzed the real-world outcomes of older women who were treated with T-DM1 therapy. Methods: We performed a multicenter, observational, retrospective analysis of patients aged > 65 years treated with T-DM1. A total of 93 patients from 10 cancer centers were involved in the study. Our goal was to determine the survival, response rates, and toxicity profile in T-DM1-treated patients, as well as the factors that influence survival. Results: Median follow-up was 12.2 months. Objective response rate was 29%. Median progression-free survival (PFS) and overall survival (OS) were 8.47 and 15.0 months, respectively. In multivariate analysis, Eastern Cooperative Oncology Group Performance Score 2 was found to be an independent prognostic factor for worse PFS (hazard ratio [HR] 1.81, p = 0.032) and OS (HR 2.33, p = 0.006). Any adverse event (AE) was seen in 92.5% of patients; grade 3 or 4 AEs were seen in 30.1%. Dose reduction or treatment discontinuation rates were 11.8% and 6.5%, respectively. Conclusion: The efficacy of T-DM1 was acceptable and it was generally well-tolerated among older patients with advanced HER2-positive breast cancer.
Keywords: HER2 positive; metastatic breast cancer; older patients; real-world; PHYSIOLOGICAL-ASPECTS; DECISION-MAKING; AGE; MANAGEMENT; SURVIVAL; IMPACT; T-DM1; WOMEN